Urdu Literature and Politics: An Inextricable Tapestry of Narrative and Power - Dr. Zahid Akhtar Shaheen,; Dr. Shazia Andleeb,; Muhammad Waseem (Azad),; Muhammad Ahmad,; Tanveer Ahmad,; Awais Ghani, (Al-Qanṭara, 2023)
This comprehensive study explores the deeply intertwined relationship between Urdu literature and the political milieu, emphasizing their mutual influence across various historical epochs in the Indian subcontinent and Pakistan. Urdu literature, known for its rich poetic tradition and extensive corpus of prose, has been an integral cultural component, articulating political resistance, fostering national identity, and reflecting social dynamics from the time of the Delhi Sultanate through the Mughal era, colonial period, and into the contemporary political landscape of Pakistan. The research initially contextualizes the advent of Urdu literature in the socio-political ambiance of the Delhi Sultanate, followed by its proliferation during the Mughal reign. This period witnessed Urdu literature, particularly poetry, gaining prominence as a tool for both subtle political dissent and endorsement within royal courts. The study examines literary contributions from iconic figures like Amir Khusrau and Mirza Ghalib, exploring how their works transcended mere artistic expression, encapsulating the political zeitgeist and societal norms. Progressing into the colonial era and the subsequent fight for independence, the paper underscores a paradigm shift where Urdu literature transitioned from the elite's cultural pastime to a force for political awakening and social reform. It discusses the works of Allama Iqbal, whose poetry fueled nationalist fervor, and Faiz Ahmed Faiz, whose leftist ideology and opposition to authoritarianism resonate in his writings. The analysis extends to Saadat Hasan Manto's poignant short stories that lay bare the chaos and human cost of Partition. Post-independence, the research delves into the evolution of Urdu literature in Pakistan, amidst alternating democratic and authoritarian regimes. The paper dissects how state narratives influenced literary expression, especially during the dictatorial reigns when literature became a subversive act, challenging state oppression and societal injustices. Herein, the study investigates the literary responses to political events like military coups, the imposition of martial law, and movements for democratic rights, highlighting the works of writers and poets who continued the tradition of dissent and social commentary. Furthermore, the research analyzes the contemporary role of Urdu literature in the political discourse, considering the impact of globalization, the War on Terror, and the digital revolution. It elucidates how contemporary Urdu literature navigates issues of identity, secularity, and radicalism, continuing its legacy as a commentator on and reflector of political dynamics. Conclusively, this study reaffirms Urdu literature not just as a vehicle of cultural expression but as an active participant in shaping and critiquing the political narrative. Through a diachronic review of literary works across different political eras, it highlights the enduring power of Urdu literature as a medium that reflects, resists, and, at times, reinforces political ideologies and actions.